TRANSDERMAL DELIVERY OF CALCIUM CHANNEL BLOCKER: DEVELOPMENT AND CHARACTERIZATION - SP, Surya Teja; Khandelwal, Manisha; V, Chitra; N, Damodharan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Felodipine, a BCS class II calcium channel blocker, is used in the management of hypertension and angina pectoris. Due to the poor solubility and low bioavailability of the drug, there is a necessity to design an alternative route to achieve a constant plasma concentration of felodipine for its maximum therapeutic utility and can be achieved by transdermal route. Methods: In this study, matrix type transdermal patches were prepared using different combinations of hydrophilic polymer, namely, polyvinylpyrrolidone (PVP) and hydrophobic polymer, namely, ethyl cellulose (EC) by solvent evaporation technique and were subjected for characterization. Results: The Fourier transform infrared studies confirmed the compatibility between drug and polymers. Hydrophilic nature of the polymers greatly influenced physical characteristics and dissolution rate. Equal percentage of PVP and EC yielded patches with good folding endurance. The concentration of plasticizer present in the patches gave them desired folding endurance, and it increased with the presence of hydrophilic polymer. The formulation with highest PVP concentration, F3, exhibited a maximum drug release of 96.23% for 24 hrs. While the formulation with highest EC concentration, F5, exhibited only 74.45% drug release for 24 hrs. Conclusion: From the data, formulation F2 (PVP/EC, 2:1) can be concluded as best formulation due to its desired physical characteristics, good initial drug release, sustained release behavior, and good in vitro permeation. This formulation can be further studied in a clinical scenario.